Leiomyoma in Vulva: A Diagnostic Dilemma - Deeksha Pandey; Jyothi Shetty; Aashish Saxena; P. S. Srilatha (Case Reports in Obstetrics and Gynecology)
With the help of this case we summarize some crucial features to be picked up from history and examination before labeling a case as Bartholin’s abscess or cyst. A 20-year old unmarried girl, deaf and mute since birth, was initially diagnosed to have Bartholin’s abscess. On careful reexamination after inflammation subsided, a decision of excision of this tumor was taken. Intraoperatively it was found to be well encapsulated. Histopathology ascertained the diagnosis of vulval leiomyoma.